Highly active and stable Pt-Ni/CeO2-SiO2 catalysts for ethanol reforming. (10th November 2017) - Palma, Vincenzo; Ruocco, Concetta; Meloni, Eugenio; Ricca, Antonio
Abstract: In this work, the Pt-Ni/CeO2 -SiO2 catalyst was prepared by wet impregnation and tested for steam and oxidative steam reforming of ethanol at low-temperature (300–600 °C). The solids were characterized by X-ray fluorescence (XRF) and diffraction (XRD), nitrogen adsorption, Raman spectroscopy, temperature programmed reduction (TPR) and oxidation (TPO). Reforming tests were carried out between 10, 000 and 30, 000 h −1, recording total conversion at T > 450 °C, independently from the contact time and the feed composition; in addition, hydrogen yield was marginally affected by O2 co-feeding, especially in the mild-temperature range. During stability tests, carried out at 500 °C and 20, 000 h −1 for at least 45 h, oxygen addition reduced carbon formation rate (CFR) of almost 30%, assuring a complete conversion for 55 h. Catalyst deposition on high surface area silica improved active species dispersion and metal-support interaction, preventing sintering phenomena and resulting in a much lesser coke selectivity than that observed for the silica-free sample. Highlights: The deposition of Pt-Ni/CeO2 on mesoporous silica improved surface area and metals dispersion. No significant effect of GHSV and air co-feeding on ethanol conversion was observed at T > 450 °C. Oxygen addition reduced CFR of almost 30% at 500 °C and 20, 000 h −1 . The SiO2 -based catalyst improved resistance to deactivation with respect to the Pt-Ni/CeO2 catalyst.